1992
DOI: 10.1111/j.1365-2125.1992.tb04118.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid antagonists and their potential for the treatment of ischaemic brain damage in man.

Abstract: 1 A wide range of therapeutic strategies has been explored in humans and experimental animals with the aim of improving outcome after brain ischaemia but few have shown convincing clinical benefit. 2 The massive increase in the extracellular concentration of glutamate which occurs in cerebral ischaemia is a key component in the sequence of neurochemical events which leads to neuronal death. Pharmacological blockade of the action of glutamate at the N-methyl-D-aspartate (NMDA) receptor, (the glutamate receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(54 citation statements)
references
References 68 publications
1
53
0
Order By: Relevance
“…The case for a clinical trial of NMDA antagonists in stroke has been clearly stated. 13 Further studies are required with non-NMDA antagonists before their clinical potential and relative merits compared with NMDA antagonists can be defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case for a clinical trial of NMDA antagonists in stroke has been clearly stated. 13 Further studies are required with non-NMDA antagonists before their clinical potential and relative merits compared with NMDA antagonists can be defined.…”
Section: Resultsmentioning
confidence: 99%
“…2 -8 - 13 Tarnawa and coworkers 14 ' 15 have recently described a novel non-NMDA antagonist, GYKI 52466 (l-(4-aminophenyl)-4-methyl-7,8-methylenedioxy-5H-2,3-benzodiazepine hydrochloride; molecular weight, 330), which inhibits spinal reflexes in cats but does not potentiate the inhibitory action of y-amino butyrate. Ouardouz and Durand 16 have shown that GYKI 52466 antagonizes the glutamate-but not the NMDA-or KA-induced electrophysiological responses in the abducens motor neurons of the rat.…”
mentioning
confidence: 99%
“…28,29) Glu, through an action on NMDA and α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptors, allows Ca 2+ to enter the cell. 30,31) Glu can The damages were evaluated by the assay of MTT and LDH release from the cultured medium. TG was added simultaneously and 12 hr prior to addition of Glu, and the cells were exposed to 1 mM Glu for 6-12 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The mean ratio of middle or anterior cerebral artery to internal carotid artery velocities (Aaslid index) was 7.4±0.5 (mean±SEM) in the 15 patients selected for SPECT who had neurological deficit (patients [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This was significantly greater than the ratio seen in the five patients who did not develop neurological deficit (4.6±0.4, /?=0.003).…”
Section: A Summary Of the Clinical And Radiological Findings For The mentioning
confidence: 99%